The relation between State and Catholic Church in Colombian social assistance: 1870 – 1960 - Castro Carvajal, Beatriz (Sociedad y Economía, 2011)
This article clarifies the relation between state and Catholic Church at social assistance in Colombia as contractual relation and presents how this legal relation was established between 1870 – 1960, throughout a research of emblematic institutional program of the Junta General de Beneficencia de Cundinamarca and the religious women congregation Sister of Charity Dominicans of Presentation.